Brazil, 2091: notes on the national literacy policy - Longo Mortatti, Maria do Rosario [UNESP] (Univ Fed Sao Paulo, Dept Education, 2019)
In order to contribute to the debate on the National Literacy Policy (PNA), instituted in Brazil, on April 11, 2019, reflections on this State Policy, from the perspective of the history of Brazilian literacy, are presented. Based on the analysis of the main aspects of the textual configuration of documental sources in which the PNA is synthesized, it is proposed to interpret its intrinsic politicity through the intersection of at least three possibilities of meanings - such as quarrel of methods, wars of methods/ideological crusade and a case of sciencefare - related with each other and with the dispute for hegemony of a neoliberal and ultra-conservative political-ideological project under implementation in the country.
Keywords: National Literacy Policy; History of literacy; Brazil